Trends in macro-marketing strategies of consumer goods multinationals a special focus on regionalization. - Sidharth Haralalka. (2008)
The basic purpose of this dissertation is to examine and describe the trends of macro marketing strategies being followed by large multinational consumer goods companies. The main objectives of the paper are (i) to determine the current macro marketing strategies being followed by multinational consumer goods companies (ii) to determine the upcoming trends in macro marketing strategies.